2010
DOI: 10.1017/s0027763000022261
|View full text |Cite
|
Sign up to set email alerts
|

Instability of one global transonic shock wave for the steady supersonic Euler flow past a sharp cone

Abstract: Abstract. In this paper, we are concerned with the instability problem of one global transonic conic shock wave for the supersonic Euler flow past an infinitely long conic body whose vertex angle is less than some critical value. This is motivated by the following descriptions in the book Supersonic Flow and Shock Waves by Courant and Friedrichs: if there is a supersonic steady flow which comes from minus infinity, and the flow hits a sharp cone along its axis direction, then it follows from the Rankine-Hugoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…For the potential equation, under various assumptions on the supersonic incoming flows and the sharp vertex angles of the conic bodies, the authors have established the local or global existence and stability of the weak conic shocks or strong conic shocks, one can see [5][6][7][8][9]15,16,19,[23][24][25]29] and the references therein. For the full Euler system, because of the essential influences of the rotations, the authors in [28] and [26] have shown the nonexistence of the global weak solution with only one stable weak conic shock and the instability of a global transonic conic shock for the steady supersonic flow past a sharp conic body, respectively. Therefore, these results have given a basic answer for the global stability or instability of weak and strong conic shocks.…”
Section: Substituting (13) Into the Mass Conservation Equationmentioning
confidence: 99%
“…For the potential equation, under various assumptions on the supersonic incoming flows and the sharp vertex angles of the conic bodies, the authors have established the local or global existence and stability of the weak conic shocks or strong conic shocks, one can see [5][6][7][8][9]15,16,19,[23][24][25]29] and the references therein. For the full Euler system, because of the essential influences of the rotations, the authors in [28] and [26] have shown the nonexistence of the global weak solution with only one stable weak conic shock and the instability of a global transonic conic shock for the steady supersonic flow past a sharp conic body, respectively. Therefore, these results have given a basic answer for the global stability or instability of weak and strong conic shocks.…”
Section: Substituting (13) Into the Mass Conservation Equationmentioning
confidence: 99%
“…It was frequently stated that the strong shock is unstable and that, therefore, only the weak shock is present in real situations. In [32][33][34], the global instability of an attached strong conic shock in the whole space was systematically studied (in this case, the corresponding subsonic potential equation is nonlinear elliptic and the steady Euler system becomes elliptic-hyperbolic) which especially showed that a global strong conic shock is actually unstable as long as the perturbation of the sharp circular cone satisfies some suitable assumptions. On the other hand, from the result in this paper, one infers the global stability of a supersonic conic shock.…”
Section: §1 Introductionmentioning
confidence: 99%